Students’ Perceptions of Android-Based Interactive Multimedia in Learning Biology - Ronal Watrianthos; Reti Handayani; Rosmidah Hasibuan; Ambiyar Ambiyar; Refdinal Refdinal (Universitas Pahlawan Tuanku Tambusai, 2022)
Multimedia that you can interact with is an important part of learning. Multimedia can be used as a learning tool to improve the quality of learning. Learning media can be used to try out different ways to teach and learn. Interactive media made for Android helps students learn more. Using this material makes a big difference in how well students learn. The goal of this study is to find out how students feel about using interactive multimedia based on Android in Biology classes at Senior High Schools after COVID-19. This study was done with 60 students from Mts Ar Royan Aek Nabara Labuhanbatu. They all filled out a questionnaire. Students were sent a questionnaire to gather information, and the results were looked at. According to the perception findings, 67 percent of students have used interactive multimedia based on Android, 69 percent of teachers use audiovisual tools to teach ideas, and 78 percent of respondents prefer to use interactive multimedia. This shows that using Android-based interactive multimedia apps could improve the quality and effectiveness of biology education during the COVID-19 epidemic.